Whole‐exome sequencing broadens the phenotypic spectrum of rare pediatric epilepsy: a retrospective study. (28th August 2014) - Dyment, D.A.; Tétreault, M.; Beaulieu, C.L.; Hartley, T.; Ferreira, P.; Chardon, J.W.; Marcadier, J.; Sawyer, S.L.; Mosca, S.J.; Innes, A.M.; Parboosingh, J.S.; Bulman, D.E.; et al.
<x xml:space="preserve">Abstract</x> Whole‐exome sequencing (WES) has transformed our ability to detect mutations causing rare diseases. FORGE (Finding Of Rare disease GEnes) and Care4Rare Canada are nation‐wide projects focused on identifying disease genes using WES and translating this technology to patient care. Rare forms of epilepsy are well‐suited for WES and we retrospectively selected FORGE and Care4Rare families with clinical descriptions that included childhood‐onset epilepsy or seizures not part of a recognizable syndrome or an early‐onset encephalopathy where standard‐of‐care investigations were unrevealing. Nine families met these criteria and a diagnosis was made in seven, and potentially eight, of the families. In the eight families we identified mutations in genes associated with known neurological and epilepsy disorders: ASAH1, FOLR1, GRIN2A (two families), SCN8A, SYNGAP1 and SYNJ1. A novel and rare mutation was identified in KCNQ2 and was likely responsible for the benign seizures segregating in the family though additional evidence would be required to be definitive. In retrospect, the clinical presentation of four of the patients was considered atypical, thereby broadening the phenotypic spectrum of these conditions. Given the extensive clinical and genetic heterogeneity associated with epilepsy, our findings suggest that WES may be considered when a specific gene is not immediately suspected as causal.